TINJAUAN YURIDIS HAK MILIK ATAS TANAH PADA PERKEBUNAN KELAPA SAWIT PERORANGAN - DEWI FATIMAH LUBIS (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Muhd Yamin2. Syafruddin Kalo3. Budiman Ginting Individual estate with the area of less than 25 hectares, according to the Regulation of the License of Plantation Business, must be registered to Regency/Mayor. For the certainty of the plantation business, besides the certificate of company registration, it also needs land registration issued by the Land Office. For the condition in North Sumatera, particularly in Labuhan Batu District, it was necessary to conduct a research on the regulation on the implementation of land registration for plantation land owned by individuals with various variables in it.Keywords: Pal Oil Plantation, Individual, Ownership